2011
DOI: 10.2224/sbp.2011.39.10.1431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Audience Response Systems on Student Achievement and Long-Term Retention

Abstract: The effects of audience response systems (ARS) on students' academic success and their perceptions of ARS were examined in this study. Participants, comprising 44 undergraduate students, were randomly assigned to a control or treatment group. The course design was the same for both groups and the instructor prepared the multiple-choice questions in advance; students in the control group responded to these questions verbally whereas the treatment group used ARS. Two paper-based examinations were used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A six-year study by Poulis, Massen, Robens, and Gilbert (1998) revealed compelling evidence that clickers integrated in physics courses significantly improved student scores on examinations. Karaman (2011) found significant improvement in learning after a four-week time period; however, long-term retention was no different between groups. Improvement in student achievement was also reported by both Mazur (1997), who used clickers to support peer instruction, and Hake (1998).…”
Section: Learners Is Challenging and Often Frustrating Formentioning
confidence: 71%
“…A six-year study by Poulis, Massen, Robens, and Gilbert (1998) revealed compelling evidence that clickers integrated in physics courses significantly improved student scores on examinations. Karaman (2011) found significant improvement in learning after a four-week time period; however, long-term retention was no different between groups. Improvement in student achievement was also reported by both Mazur (1997), who used clickers to support peer instruction, and Hake (1998).…”
Section: Learners Is Challenging and Often Frustrating Formentioning
confidence: 71%
“…However, while some papers highlighted the significance of the immediacy of intervention, they also found no replication of results at follow-up stages (Doucet et al 2009;Liu et al 2010;Karaman 2011, Tregonning et al 2012 suggesting that it is most effective for immediate retention of facts (Anderson et al 2013). Additionally, Shapiro and Gordon (2012) suggest that utilisation of clickers for factual multiple-choice questions appears to enhance memory for delayed factual test questions.…”
Section: Computer-based Assessmentmentioning
confidence: 99%
“…Supporting this use are a variety of papers reporting the benefits to students of ARS (Oliveira, Binda, Lopes & Vaile, 2017;Giacalone, 2016). However, many papers suggest that whilst students perceive ARS positively, there is no actual benefit to student learning (Funnell, 2017;Karaman, 2011). Kay and LeSage (2009) conducted a literature review on the use of ARS concluding that much of the evidence was based on questionable methods, with the majority of ARS investigations consisting of "broad assessments of attitude and/or anecdotal observations" (p825).…”
Section: Epoch 3: E-learning and The Internet -Late 1990s To Mid 2000smentioning
confidence: 99%